2002
DOI: 10.4141/s01-023
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal extractability in soils and uptake by bromegrass 20 years after sewage sludge application

Abstract: . 2002. Trace metal extractability in soils and uptake by bromegrass 20 years after sewage sludge application. Can. J. Soil Sci. 82: 323-333. The long-term potential for sewage sludge amendments to alter forage trace metal concentrations was determined on bromegrass, which received no sludge application for 20 yr following annual application during 1973-1980 on a no-till randomized-plot experimental site. In addition, soils were analyzed for trace metals, both total and extractable (using hot 0.01 M CaCl 2 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
12
1
3
Order By: Relevance
“…In contrast, Gaskin et al [26] reported that SOC levels were not different between bermudagrass fields receiving repeated surface applications for <6 yr or for >6 yr, though SOC levels in both treatments were higher than unamended fields. Longterm gains in SOC have been reported in other studies which found that increased SOC or SOM levels can persist up to 27 yr after biosolids applications have ceased [24,25,29,[34][35][36].…”
Section: Soil Organic Carbon and Total Nitrogen Stocksmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, Gaskin et al [26] reported that SOC levels were not different between bermudagrass fields receiving repeated surface applications for <6 yr or for >6 yr, though SOC levels in both treatments were higher than unamended fields. Longterm gains in SOC have been reported in other studies which found that increased SOC or SOM levels can persist up to 27 yr after biosolids applications have ceased [24,25,29,[34][35][36].…”
Section: Soil Organic Carbon and Total Nitrogen Stocksmentioning
confidence: 87%
“…Other field studies on repeated surface-applied biosolids also have found increases in SOC [4,12,[24][25][26][27]29] and found that increases are positively correlated with application rate [4,25]. Site-specific increases in SOC have been reported for application rates as low as 2 to 7 Mg ha −1 yr −1 [24,30].…”
Section: Soil Organic Carbon and Total Nitrogen Stocksmentioning
confidence: 93%
“…Důležitým výsledkem je potvrzení v literatuře prezentovaného předpokladu, že vysoký celkový obsah zinku v půdě nemusí automaticky znamenat vysoké obsahy v pěstovaných rostlinách (McBride et Evans, 2002;Schaecke et al, 2002). Jedinou výjimkou byly poměrně vysoké koncentrace ve špenátu.…”
Section: Vegetační Pokusunclassified
“…Ukazuje to na vysokou srovnatelnost výsledků dosahovaných s použitím těchto vyluhovadel. Zcela v souladu s literárními prameny (Chander et Brookes, 1993;Guang Wen et al, 2002;McBride et Evans, 2002) je potvrzen efekt použitých kalů (půda Chrlice) na zvýšení podílů méně stabilních (potenciálně mobilizovatelných) frakcí zinku v půdě. Ačkoli celkový obsah není extrémně vysoký, téměř čtvrti-na je vyluhovatelná roztokem DTPA.…”
Section: Vegetační Pokusunclassified
See 1 more Smart Citation